The Effect of Using the Graphic Organizers Strategy on Visual Thinking Skills Among First-Grade Intermediate Students in Mathematics (Journal of the College of Basic Education, 2025)
The aim of the research was to identify the effect of using the graphic organizers strategy on the visual thinking skills of first-grade intermediate students in mathematics. To achieve this goal, the researcher adopted the experimental research method and used a quasi-experimental design with partial control for two equivalent groups, using a post-test to measure visual thinking skills. The experiment was conducted on a sample of 53 students: 27 in the experimental group and 26 in the control group, all from Al-Akhtal Intermediate School for the academic year 2024–2025.The two groups were equalized based on several variables: prior knowledge in mathematics, students’ chronological age in months, previous academic achievement in mathematics, a visual thinking skills test, and an intelligence test. The researcher prepared the necessary requirements for the experiment, which included identifying the instructional content, analyzing it, formulating behavioral objectives, and preparing teaching plans. A visual thinking skills test was constructed, consisting of 20 multiple-choice items. The test’s validity was verified, and it demonstrated an acceptable reliability coefficient. The difficulty and discrimination indices of the test items, as well as the effectiveness of the distractors, were all satisfactory.The experimental group was taught using the graphic organizers strategy, while the control group was taught using the traditional method. After the experiment concluded, the visual thinking skills test was administered to both the experimental and control groups, and several appropriate statistical methods were used for data analysis.The results showed a statistically significant difference at the 0.05 level between the mean scores of the experimental group and those of the control group in the visual thinking skills test, in favor of the experimental group.Several conclusions were drawn, including that teaching mathematics using the graphic organizers strategy improved the achievement of the students in the experimental group and positively impacted the development of their visual thinking skills.The researcher also recommended encouraging teachers to focus on teaching thinking in general, and visual thinking and its skills in particular, as it is a mental activity linked to the most important sense through which students learn—sight. In addition, the importance of training teaching staff in elementary, intermediate, and secondary schools to apply the graphic organizers strategy in teaching mathematics was emphasized.Several suggestions were proposed, including conducting similar studies at other educational stages, and investigating the effect of the strategy on other dependent variables, such as the development of formal thinking, systems thinking, and geometric thinking in mathematics